1973
DOI: 10.1042/cs0450775
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Ouabain-Sensitive Adenosine Triphosphatase Activity in the Erythrocyte Membrane of Patients with Chronic Renal Disease

Abstract: 1.Ouabain-sensitive ATPase (adenosine triphosphatase) activity was measured in the erythrocyte membranes of twenty patients with chronic renal disease. Decreased activity was found in nineteen of the twenty patients. The average decrease was 38%.2. In three patients erythrocyte sodium concentration exceeded 9.5 mmol/l of RBC and these patients had the most marked decreases in ouabain-sensitive ATPase activity.3. By contrast, in only two of 100 patients admitted to a general medical ward was erythrocyte sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

1976
1976
1991
1991

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 8 publications
6
42
0
Order By: Relevance
“…The data for this patient were not included in the statistical analysis as he was found to be an outlyer by using the BMDP statistical software package. 13 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data for this patient were not included in the statistical analysis as he was found to be an outlyer by using the BMDP statistical software package. 13 …”
Section: Resultsmentioning
confidence: 99%
“…The ATPase activity was assayed 13 in a medium containing 0.3 to 0.5 mg of erythrocyte per milliliter, 50 mM Tris (pH 7.4 at 37°Q, 6 mM MgCl ? , 100 mM NaCl, 20 mM KC1, 6 mM adenosine 5'-triphosphate (ATP) and 0.5 mM EGTA and a medium containing the same components plus 0.2 mM ouabain.…”
Section: Measurement Of Na+k + -Atpase Of Erythrocytesmentioning
confidence: 99%
“…In Table 2 (Wilkinson, 1975) (Welt, Smith, Dunn, Czerwenski, Proctor, Cole, Balfe & Gitelman, 1967;Cole, Balfe & Welt, 1968;Cole, 1973). They have found that the plasma of uremic patients contains a dialysable substance which inhibits Na +-K +-ATPase activity in normal human erythrocytes but that this inhibition occurs predominantly when the plasma is that of uremic patients with high intraerythrocytic sodium concentrations (Cole et aL, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in intracellular Na was first described in erythrocytes from some patients with chronic renal failure some two decades ago (5). Subsequently, several groups of investigators have provided evidence for a defect in Na transport of erythrocytes (6)(7)(8)(9), leukocytes (10), and skeletal muscle ( 11) from uremic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier efforts to explore the mechanism of the rise in intracellular Na were limited to measurements of pumpmediated Na efflux, the passive Na leak, and Na-K-ATPase activity (5)(6)(7)(8)(9)(10)(11)(12). In the present study, the number of Na-K pump sites was quantitated by the technique of [3H]ouabain binding (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%